Doctoral Theses from Nursing Postgraduate Programs in Brazil and their Association with the Millennium Development Goals - Rosalina Aparecida Partezani Rodrigues; Maria Lúcia do Carmo Cruz Robazzi; Alacoque Lorenzini Erdmann; Josicélia Dumet Fernandes; Alba Lucia Bottura Leite de Barros; Flávia Regina Souza Ramos (Universidade de São Paulo, 2015)
OBJECTIVES: The Millennium Development Goals are centered around combatting poverty and other social evils all over the world. Thus, this study seeks to identify the Millennium Development Goals as an object of study in theses from Postgraduate Nursing Programs in Brazil scoring 5 (national excellence) and 6 or 7 (international excellence), and evaluate the association between the score for the program and achieving the Millennium Development Goals.METHOD: Exploratory descriptive document research. Data were collected from the Notes on Indicators/Coordination for Higher Education Personnel Improvement for the 15 Postgraduate Nursing Courses scoring between 5 and 7 in the three-year-period of 2010/2012.RESULTS: of the 8 Millennium Development Objectives, 6 were dealt with in the theses. There was an association (Fisher's exact test p-value=0.0059) between the distribution of the theses and the program scores in relation to the Millennium Development Objectives (p-valor=0.0347)CONCLUSION: the doctoral theses were slightly related to the Millennium Development Objectives, covering the population's economic development, health conditions and quality of life. It is recommended that Postgraduate Programs in Nursing pay closer attention to the Millennium Development Objectives..